Pengaruh Religious Commitment terhadap Place Attachment pada Rumah Ibadah - Jessica Amanda Gabriella Siahaan; Rika Eliana (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The This study aims to examine the effect of religious commitment on attachment to a place of worship. Emotional attachment to a place affects a person's emotions, including to a place of worship. A person who has an attachment to a place will also affect the frequency of his activities in that place. and can also reduce stress. The research method used in this study is descriptive quantitative with an incidental sampling method. The sample in this study amounted to 197 subjects. Data collection used a Likert scale, namely the scale of religious commitment and place attachment. The analysis method used is a simple regression analysis method. Based on the results of the study, the Tcount value is 10.676 and it is known that Ttable is equal to 1.645. It is said that Tcount is greater than Ttable, so the alternative hypothesis in this study is accepted. The results of this study indicate that there is an effect of religious commitment on place attachment in a place of worship.